О некоторых приложениях интегральных преобразований - Есенбаева, Г.А. (Изд-во КарГУ, 2010)
Мақалада жылуөткізгіштік пен толқындық теңдеуінің шарттары берілген, олардың қасиеттері, сонымен қатар қарастырылған теңдеулердің шеттік есептерінің шешімі интегралдық Фурье түрлендіруін қолданып, зерттелпен. In the given article the equation of heat conduction, the wave equation with the given conditions, some properties of these equations and also the solutions of study boundary problems for these equations with the application of integral transformation of Fourier have been investigated.
About some applications of integral transformations